Influence of acculturation strategies on the judgement and punishment of an offender of North African descent. Issue 9 (21st October 2017) - Taillandier-Schmitt, Anne; Combalbert, Nicolas
ABSTRACT: Very few studies have examined the influence of the acculturation strategies of an offender of foreign descent on the way a third party judges the personality and action of that offender. The aim of our study was thus to measure the effect of three variables (Seriousness of the harm suffered by the victim; Type of acculturation strategy of the offender; Level of Social Dominance Orientation [SDO]) of the person making the judgement) on the judgements and decisions made by a sample of students faced with a situation of physical aggression committed by a man of North African descent living in France. After reading a scenario describing a criminal act committed by a man of North African descent, who had or had not adopted French culture, 168 French students completed a judgement scale concerning the criminal act and the offender and an SDO scale. The results show that the crime was perceived as less serious when the perpetrator had adopted French culture than when he had not. The perpetrator was also judged less severely. Participants with higher levels of SDO advocated harsher punishment and attributed the crime to the offender's personality. We discuss these results and identify new avenues for research.